Office 2007 for dummies - Wang, Wally (--For dummies., 2007)
Find and use the features you need right away Create great documents, Excel charts, and slide shows, and organize your e-mail What's new at the Office? A lot, and this book takes you through all the cool changes and enhancements so you can rev up and go. Find your way around the new interface, dress up your documents, create spreadsheets that actually make sense, give presentations that wow your audience, and organize your life. Discover how toLocate commands on the RibbonUse Live PreviewStop spam with Outlook(r)Format and enhance Word documents<l.